The effectiveness of artificial enteral nutrition in intensive care unit patients - Papagiannopoulos, Ioannis; Marvaki, Aikaterini; Kavoura, Paraskevi; Papagiannopoulos, Sotirios; Lagiou, Anthoula; Dokoutsidou, Eleni (Health & Research Journal, 2015)
Introduction: The artificial enteral nutrition is an important therapeutic intervention for the prevention of the effects of starvation and the positive effect on the final outcome of the disease. Aim: The aim of this study was to investigate the efficacy of artificial enteral nutrition as they are assessed by laboratory nutritional markers. Material and Methods: The studied sample consisted of 70 patients who were hospitalized in the Intensive Care Unit General Hospital in Athens from June 2013 to June 2014. For data collection a special registration form with information derived from medical records of patients was used. Results: Τhe majority of the studied sample were male (61,4%, n=43), with a mean age of 56.3 years and an average hospital stay of 25.5 days. In most cases the possible diagnosis was consistent with the final diagnosis in most patients the sample to be blunt trauma (24,6%, n= 14) or have respiratory failure (19.3%, n = 11) CCIcerebral hemorrhage (26,3% n=15). All patients received Special Diet preparation(1,5 kcal / ml) within the first 48 hours of admission with a mean duration of enteral nutrition 24 days and average time for tracheostomy six days after admission. The most common mechanical complications were nostril ulceration (65.6%, n=44), reflux and aspiration (4.4%, n=3) and nasogastric tube leaking(1,5%, n=1) Most common gastrointestinal complications were diarrhea (80.9%, n = 55), abdominal pain (29.9%, n = 20), nausea (13.4%, n=9) and bowel distension (32.4%, n=22), while most common metabolic complications were hyperglycemia (40.9%, n=21), fluid overload (7.4%, n=5) and the electrolyte disturbances (27.9%, n=19). Regarding to laboratory markers was effectuated three consecutive weekly blood tests. The results of the statistical analysis leading to the conclusion that the total proteins , albumins, platelets and the absolute lymphocyte count are the laboratory markers which vary significantly over these tests, and hence the positive outcome of enteral nutrition. Conclusions: The results of this study contribute to the identification of laboratory markers that act as important determinants of the effectiveness of artificial enteral nutrition in hospitalized patients in Intensive Care Units.